Association between serum-free thyroxine level and all-cause mortality in critically ill patients: a retrospective study from MIMIC-IV - Dai, Juan-Juan; Du, Ding-Fu; Ma, Gang; Jiang, Ming-Jie (Frontiers in Endocrinology, 2023)
Background Low thyroxine (T4) levels have been observed in critically ill patients; however, controversial results regarding T4 supplemental therapy are reported. The association between serum free T4 (FT4) levels and mortality in critically ill patients has not been fully established and needs to be clarified. Methods Data from the Medical Information Mart for Intensive Care (MIMIC)-IV were collected and analyzed. The association between FT4 level and 30-day mortality after ICU admission was analyzed using Kaplan–Meier curves, spline smoothing fitting, martingale residuals of the null Cox model, and restricted cubic spline (RCS). Logistic regression, Cox regression, and receiver operating characteristic curve (ROC) were used to uncover the relationship and predictive value of serum FT4 and 30-day mortality in critically ill patients. Results In the final analysis, 888 patients were enrolled, and the serum FT4 levels were divided into four groups. A significant difference in 30-day mortality was observed between the four groups. Kaplan–Meier curves also presented significantly higher 30-day mortality in groups 1 and 2 (p < 0.0001). Further multivariance logistic regression showed that group 1 with FT4 levels lower than 0.7 μg/dl can predict 30-day mortality (odds ratio (OR) = 3.30, 95% confidence interval (CI) = 1.04–11.31). Spline smoothing fitting analysis showed a “V”-shaped line between 30-day mortality and FT4 level within 0–3 μg/dl. Further RCS analysis showed that the risk of death decreased rapidly as FT4 levels increased when serum FT4 levels were lower than 1.2 μg/dl and started to become flat afterward. The area under the ROC of the lower FT4 level to predict 30-day mortality was 0.833 (95% CI = 0.788–0.878). Both multivariant Cox regression and logistic regression showed that FT4 levels lower than 1.2 μg/dl can independently predict 30-day mortality when adjusted for other potential confounders (HR = 0.34, 95% CI = 0.14–0.82; OR = 0.21, 95% CI = 0.06–0.79, respectively), but its predictive power disappeared when adjusted for T3 or total T4. Conclusion Serum FT4 levels were significantly negatively associated with 30-day mortality when they were lower than 1.2 μg/dl and could predict the risk of 30-day mortality. A higher FT4 level is potentially related to increased 30-day mortality.